"Carbon diffusion" engineered carbon nitride nanosheets for high-efficiency photocatalytic solar-to-fuels conversion. (September 2022) - Chen, Ruijie; Zhang, Zhiqiang; Wu, Jun; Chen, Xueru; Wang, Lei; Yin, Haotian; Li, Hongping; Ding, Jing; Wan, Hui; Guan, Guofeng
Abstract: The fabrication of graphitic carbon nitride (g-C3 N4 ) has received much attention for its superior photoelectronic properties, it remains a remarkable challenge with a feasible methodology. Herein, inspired by carburization, a novel method with carbon diffusion was proposed to prepare g-C3 N4 nanosheets (CNNS). The carbon diffusion was caused by the gradient difference in carbon concentration between the gaseous environment and the C15 (mild steel with low carbon content) during thermal polymerization. Eventually, the CNNS with approximately 1.5 nm thickness was successfully fabricated and exhibited larger surface area (98.08 m 2  g −1 ), which was 15.42 times higher than that of bulk g-C3 N4 (BCN). In the evaluation of photocatalytic CO2 reduction activity, the CH3 OH formation rate over CNNS (2.10 μmol g −1  h −1 ) was 3.28 times greater than BCN. Meanwhile, the designed CNNS exhibited dramatic improvement on H2 evolved rate (HER) of 2507.02 μmol g −1  h −1, which was 6.99 times higher than BCN. More importantly, the C15 possessed the advantage of 10 times recycled to use for the fabrication of CNNS accompanied by a moderate decrease of HER. Moreover, the density functional theory (DFT) calculations were carried out based on the results. This work highlights an ingenious tactic with carbon diffusion for preparing CNNS towards renewable solar energy conversion. Graphical abstract: Herein, we reported an inducing carbon diffusion strategy for fabricating g-C3 N4 nanosheets to realize effectively solar energy conversion. Image 1